Strategien zur transformation von dienstleistungen auf informationstechnologie am beispiel der wirtschaftsprüfer in der Europäischen Union - Wittsiepe, Richard; Ginevičius, Romualdas (Journal of Business Economics and Management, 2003)
Strategy of based on information technologies services' transformation: case study of European Union's analystsCurrently implementation of informational society is seen by European Commission as important factor, which could lead to improving of compatriots’ living standards. Despite number of internet users exceeds 50 millions, it still makes only as much as one third of that number in USA. Consequently questions related to information technologies Services’ transformation strategy have become of prime importance. Presented paper deals with the issue on basis of Web Trust Assurance Service methodic proposed by American Institute of Certified Public Accountants (AICPA). This new system embraces four following areas: needs of clients, mega trends, informational technologies and auditors’ competence. Analysis shows that contemporary financial statement audit system doesn't meet requirements of investors, creditors and other users. At first, it is not of prime importance. The second, auditors are expected to perform their tasks only formally. The third, notion of auditor's independence remains obscure. The new audit system is more oriented to informational technologies. It includes determination of informational aspects, which are necessary for performance of audits’ functions, also determination of potential clients’ groups, development of new norms, criteria and etc. In this system the main role has been played by auditors. In the paper it has been emphasized that adoption of the system in Baltic countries would accelerate integration into European Union.Article in German.First Published Online: 14 Oct 2010